Is There Any Non-functional Training? A Conceptual Review - Ide, Bernardo N.; Silvatti, Amanda P.; Marocolo, Moacir; Santos, Clarcson P. C.; Silva, Bruno V. C.; Oranchuk, Dustin J.; Mota, Gustavo R. (Frontiers in Sports and Active Living, 2022)
This conceptual review investigates whether functional training (FT) is a different approach from traditional strength, power, flexibility, and endurance (aerobic or cardiorespiratory) training already adopted in the physical training plan of professional, recreational athletes, healthy, and older adults. The 20 most recent papers published involving FT were searched in the PubMed/Medline database. Definition, concepts, benefits, and the exercises employed in FT programs were analyzed. The main results were: (a) there is no agreement about a universal definition for FT; (b) FT programs aim at developing the same benefits already induced by traditional training programs; (c) exercises employed are also the same. The inability to define FT makes the differentiation from traditional training programs difficult. Physical training programs can be easily described and classified as strength, power, flexibility, endurance, and the specific exercises employed (e.g., traditional resistance training, ballistic exercises, plyometrics and Olympic-style weightlifting, continuous and high-intensity interval training). This apt description and classification may provide consistent and clear communication between students, coaches, athletes, and sports scientists. Based on the current evidence and to avoid confusion and misconceptions, we recommend that the terms FT, high-intensity FT, and functional fitness training no longer describe any physical training program.